The utilization of sulfite-rich Spray Dryer Absorber Material in portland cement concrete. (20th July 2019) - Sharifi, Naser P.; Jewell, Robert B.; Duvallet, Tristana; Oberlink, Anne; Robl, Tom; Mahboub, Kamyar C.; Ladwig, Ken J.
Highlights: Utilization potential of Spray Dryer Absorber Material (SDAM) as an additive in concrete was determined. A 20 wt% replacement of OPC with SDAM yielded a concrete that met the desirable 28-day performance criteria. The results provide evidence against the stigma of poor durability when using SDAM in concrete. Abstract: The objective of this study was to determine the utilization potential of Spray Dryer Absorber Material (SDAM) as an additive in concrete made with portland cement. Utilizing SDAM for beneficial use such as portland cement replacement reduces the CO2 impact for every cubic meter of concrete placed, and provides a means for utilities to avoid the impacts of landfilling. The utilization of SDAM in concrete is often avoided due to delay in setting time, i.e. early-age strength-gain, and expansion related durability issues. The study included SDAM collected from five different coal combustion utilities. A series of laboratory experiments were conducted on the fresh and hardened concrete made by replacing 20 wt% of the portland cement. The findings of this research demonstrates that despite slow strength gain at early ages, a 20 wt% replacement of portland cement yielded a concrete that met the desirable 28-day performance criteria. Additionally, the incorporation of SDAM containing elevated levels of fly ash content improved the resistance to chloride permeability, and autoclave expansion resistance of concrete. These results provide evidence against the stigma of poor durability when using SDAM in concrete.